Reactive toughening of injection-molded polylactide pieces using maleinized hemp seed oil. (January 2018) - Quiles-Carrillo, L.; Blanes-Martínez, M.M.; Montanes, N.; Fenollar, O.; Torres-Giner, S.; Balart, R.
Graphical abstract: Highlights: Maleinized hempseed oil (MHO) increases toughness of polylatcide (PLA). MHO increases thermal stability of PLA. MHO contributes to high environmentally friendly PLA formulations. MHO minimizes cold crystallization of PLA. MHO gives balanced mechanical resistance and ductility to PLA. Abstract: The present study describes the effect of maleinized hemp seed oil (MHO) on the physical performance of polylactide (PLA) pieces. To this end, PLA pieces with varying MHO contents in the 0–10 wt% range were manufactured by twin-screw extrusion (TSE) followed by injection molding. The resultant pieces were characterized in terms of their mechanical, thermal, and thermomechanical properties. The obtained properties suggested that, unlike typical plasticizers, MHO does not only induce an increment in elongation at break and impact resistance but it also enhances both elastic modulus and tensile strength. In addition, a moderate decrease in the glass transition temperature (Tg ) was observed. This was ascribed to simultaneous linear chain-extension, branching, and/or cross-linking phenomena due to the reaction of the multiple maleic anhydride (MAH) groups present in MHO with the terminal hydroxyl groups of the PLA chains. Furthermore, morphology characterization revealed that, though certain phase separation occurred at its highest content, MHO was finely dispersed as submicron droplets within the PLA matrix contributing to improving toughness. The use of multi-functionalized reactive vegetable oils thus represents a highly sustainable solution to reduce the intrinsic brittleness of PLA materials without compromising their mechanical resistance and the toughened biopolymer pieces described herein can find interesting applications in, for instance, rigid packaging.